PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) PADA MATERI GETARAN DAN GELOMBANG UNTUK MELATIHKAN KETERAMPILAN KOLABORASI SISWA - Fauziah, Aizzatun Nuraini; Sudibyo, Elok (PENSA E-JURNAL: PENDIDIKAN SAINS, 2023)
This study aimed to describe students' collaboration skills with the application of NHT type cooperative learning models to vibrational and wave materials. This study used quantitative descriptive with One Shot Case Study design. The subject of this study was class VIII in one of the public junior high schools in Sidoarjo regency. Data collection techniques use observation when learning using observation sheets collaboration skills. The results showed that at the first meeting the average collaboration skills were 73 with the collaborative category and the second meeting was 88 with the very collaborative category. The conclusion of this study is that the NHT learning model has an influence on students' collaboration skills on vibration and wave material.